1, 3-dichloro-5, 5-dimethylhydantoin promoted esterification of carboxylic acids under mild conditions. (7th December 2022) - Dong, Qing; Huang, Qingqiu; Wang, Mengke; Chen, Hongyan; Zi, You; Huang, Weichun
Graphical abstract: A novel and practical method has been discovered for the synthesis of esters from carboxylic acids promoted by 1, 3-Dichloro-5, 5-dimethylhydantoin. Reactions proceed smoothly under mild conditions and show high efficiency with good to excellent yields. Abstract: A novel and practical method has been discovered for the synthesis of esters from carboxylic acids promoted by 1, 3-dichloro-5, 5-dimethylhydantoin. Reactions proceed smoothly under mild conditions and show high efficiency with good to excellent yields. A series of carboxylic acids including simple molecules, drugs and amino acids are applicable to this method.